Efficacy of parecoxib as locally infiltrated analgesia with epidural analgesia infusion against epidural analgesia infusion alone in total knee arthroplasty - Faisal bin Mohd Noor (Kulliyyah of Medicine, International Islamic University Malaysia, 2016)
This is a prospective single-blinded randomized clinical trial to compare use of a combination of periarticular locally infiltrated analgesia with epidural analgesia infusion to epidural analgesia infusion alone in total knee arthroplasty (tka) patients. Fifty six patients with primary osteoarthritis who was scheduled for a unilateral total knee arthroplasty was randomly assigned into either the experimental group or control group. The periarticular injection, containing a mixture of parecoxib, ropivacaine, morphine and adrenaline, was given intra-operatively to the experimental group. The experimental group had a lower pain score at the first 24 hours post-operative (p=0.03), earlier time to achieve 90 degrees passive knee flexion (p=0.001) with a length of hospital stay not more than three days post-operation (p=0.001). Overall, the group receiving periarticular locally infiltrated analgesia had less pain in the acute setting, less epidural analgesia drug usage, earlier range of motion knee exercise, and shorter hospital stay.